2020
DOI: 10.1097/eja.0000000000001222
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid block and ultrasound-guided transversalis fascia plane block for caesarean section

Abstract: BACKGROUND After caesarean section, maternal postoperative comfort is critical to allow the new mother to care for her baby. Insufficient pain relief during the postoperative period may delay maternal/infant bonding and, in addition, such pain has been linked to subsequent depression and chronic pain. Caesarean section is commonly performed with a Pfannenstiel incision, and a transversalis fascia plane (TFP) block provides postoperative analgesia in the T12 and L1 dermatomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…Safety-related outcomes of local anesthetic techniques may include opioid-related side effects (ie, PONV, pruritus, sedation, respiratory depression, hypotension, and urinary retention), block-related complications (ie, hematoma, organ injury, local anesthetic systemic toxicity, and block failure), and effects on breastfeeding or mother-infant interaction. 84–86 Respiratory depression, 14 , 37 , 51 , 78 hypotension, 32 , 37 , 38 , 53 urinary retention, 31 , 37 , 68 , 72 effects on breastfeeding or mother-infant interaction, 43 , 65 , 77 and block-related complications 37 , 39 , 41 , 43 , 50 , 73 , 80 were rarely reported in the involved study. Therefore, we selected PONV, pruritus, and sedation as the safety outcomes of this NMA.…”
Section: Discussionmentioning
confidence: 98%
“…Safety-related outcomes of local anesthetic techniques may include opioid-related side effects (ie, PONV, pruritus, sedation, respiratory depression, hypotension, and urinary retention), block-related complications (ie, hematoma, organ injury, local anesthetic systemic toxicity, and block failure), and effects on breastfeeding or mother-infant interaction. 84–86 Respiratory depression, 14 , 37 , 51 , 78 hypotension, 32 , 37 , 38 , 53 urinary retention, 31 , 37 , 68 , 72 effects on breastfeeding or mother-infant interaction, 43 , 65 , 77 and block-related complications 37 , 39 , 41 , 43 , 50 , 73 , 80 were rarely reported in the involved study. Therefore, we selected PONV, pruritus, and sedation as the safety outcomes of this NMA.…”
Section: Discussionmentioning
confidence: 98%
“…Several clinical trials have demonstrated that the TFP block is associated with good postoperative analgesia with reduced analgesic consumption after iliac crest bone graft harvesting [ 5 ] and cesarean section [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic efficacy of TFP block have been demonstrated in adults' surgeries, including iliac crest bone graft harvesting [5], inguinal herniorrhaphy [6] and caesarean section [7,8]. In pediatric surgery, the only report of TFP block was described by Ahiskalioglu et al [9] in two children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations